2019
DOI: 10.12659/ajcr.913645
|View full text |Cite
|
Sign up to set email alerts
|

Acute Colonic Pseudo-Obstruction Caused by Dexmedetomidine: A Case Report and Literature Review

Abstract: Patient: Male, 50Final Diagnosis: Acute colonic pseudo-obstructionSymptoms: Abdominal pain • cough • feverMedication: —Clinical Procedure: Colonoscopy decompression and colectomySpecialty: Critical Care MedicineObjective:Rare co-existance of disease or pathologyBackground:Acute colonic pseudo-obstruction (ACPO) is an infrequent entity characterized by non-toxic, non-mechanical, abrupt, functional dilation of the colon. Clinically patients present with abdominal distention, anxiety, severe abdominal pain, nause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Ultrasonic acquisition equipment has developed from mechanical scanning to electronic scanning and from one-dimensional probes to two-dimensional array probes. However, a large amount of ultrasound data obtained cannot be used [ 11 ]. In this context, 3D reconstruction technology emerged and became a hot spot in current research.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic acquisition equipment has developed from mechanical scanning to electronic scanning and from one-dimensional probes to two-dimensional array probes. However, a large amount of ultrasound data obtained cannot be used [ 11 ]. In this context, 3D reconstruction technology emerged and became a hot spot in current research.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Pérez-Lara et al reported a similar case of dexmedetomidine-induced ACPO [ 19 ]. Awareness of that report leads to early suspicion that dexmedetomidine might be the culprit, primarily when the second exposure was associated with increased NG tube output.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas obstetric causes included cesarean (the most common), obstetric hemorrhage, multiple pregnancies, and preterm labor. Some medications are found to cause ACPO as narcotics, tricyclic antidepressant, antiparkinsonian drugs, Syntocinon and Dexmedetomidine [8,9].…”
Section: Epidemiologymentioning
confidence: 99%
“…Therefore, symptoms of ACPO are usually missed resulting in late diagnosis with increased morbidity and mortality. There are few reports of a potential association with ACPO [9,25].…”
Section: Dexmedetomidine-induced Acpomentioning
confidence: 99%